DESTRUCTIVE PNEUMONIA WITH PURULENT COMPLICATIONS IN CHILDHOOD - Kadirov K.Z. (Scholar Express Journals, 2025)
Acute purulent-destructive pneumonia and its complications in children remain an urgent medical and social problem. Severe course of the disease, abundance of complications and high lethality make this pathology one of the most urgent problems of pediatrics.
Keywords: Acute purulent-destructive pneumonia; early diagnosis